The art of capital restructuring : creating shareholder value through mergers and acquisitions - Baker, H. Kent (Harold Kent), 1944-; Kiymaz, Halil, 1964- (Robert W. Kolb series in finance., 2011)
The most up-to-date guide on making the right capital restructuring moves -- The Art of Capital Restructuring provides a fresh look at the current state of mergers, acquisitions, and corporate restructuring around the world. The dynamic nature of M & As requires an evolving understanding of the field, and this book considers several different forms of physical restructuring such as divestitures as well as financial restructuring, which refers to alterations in the capital structure of the firm. The Art of Capital Restructuring not only explains the financial aspects of these transactions but also examines legal, regulatory, tax, ethical, social, and behavioral considerations. In addition to this timely information, coverage also includes discussion of basic concepts, motives, strategies, and techniques as well as their application to increasingly complex, real-world situations. Emphasizes best practices that lead to M & A success - Contains important and relevant research studies based on recent developments in the field - Comprised of contributed chapters from both experienced professionals and academics, offering a variety of perspectives and a rich interplay of ideas Skillfully blending theory with practice, this book will put you in a better position to make the right decisions with regard to capital restructuring in today's dynamic business world.